Neuro-Muscular Control of Coordinated and Effective Movements: Revisiting Modular Concepts in the CNS - Mahato, Niladri Kumar (Journal of Bangladesh Society of Physiologist, 2015)
Neurophysiologic analysis of motor behavior has become one of the prime research areas in the domain of Physiology and hence it has seen tremendous development integrated research in this field over the years. This short review discusses the broad approaches which favors to understand effective neural control of motor behavior. The focus of this review is to recognize the gradual evolution of basic ideas regarding execution of coordinated and effective movements. The integrated roles of the spinal cord, the cerebellum and the motor cortex in context of voluntary movements have been delineated with citation of important research observations made in the field of motor control. Internet database related to human motor behavior studies were extensively searched to map the chronological development of important research methods and newer findings in this field. The span of the text ranges from the development of the idea of Motor Primitives to Brain-Machine Interfaces. It is observed that several basic neural modules are preserved through ontogeny and phylogeny. Different combination of hierarchical modular functioning provides a wide range of plasticity required for coordinated and effective skillful movements. DOI: http://dx.doi.org/10.3329/jbsp.v9i1.22795 Bangladesh Soc Physiol. 2014, June; 9(1): 42-47